1995
DOI: 10.1212/wnl.45.11.2058
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and characteristics of dual pathology in patients with lesional epilepsy

Abstract: We studied 167 patients who had identifiable lesions and temporal or extratemporal partial epilepsy. Pathology included neuronal migration disorders (NMDs) (48), low-grade tumors (52), vascular malformations (34), porencephalic cysts (16), and gliotic lesions as a result of cerebral insults early in life (17). MRI volumetric studies using thin (1.5- or 3-mm) coronal images were performed in all patients and in 44 age-matched normal controls. An atrophic hippocampal formation (HF), indicating dual pathology, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
136
4
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(153 citation statements)
references
References 43 publications
6
136
4
7
Order By: Relevance
“…We have detected HA by visual analysis in 70% of the patients in the group of cystic lesions and in 77,7% in the group of atrophic lesions. Although the frequency of HA in both groups was much higher than in the series of Cendes et al 5 , we found no significant difference between our two groups.…”
Section: Discussion Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…We have detected HA by visual analysis in 70% of the patients in the group of cystic lesions and in 77,7% in the group of atrophic lesions. Although the frequency of HA in both groups was much higher than in the series of Cendes et al 5 , we found no significant difference between our two groups.…”
Section: Discussion Discussioncontrasting
confidence: 87%
“…A previous study in patients with temporal and extratemporal lesional epilepsy of different etiologies, showed that cystic and atrophic lesions had associated HA in 31 and 23.5% of patients respectively, suggesting a vascular pathogenesis to HA in these cases 5 . We have detected HA by visual analysis in 70% of the patients in the group of cystic lesions and in 77,7% in the group of atrophic lesions.…”
Section: Discussion Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[7][8][9][10] In a subset of these tumors, which are generally low-grade glial or glioneuronal neoplasms, multiple pathologies, which potentially may contribute to the genesis of these seizures, are identifiable (dual pathology). [11][12][13][14][15][16] Among these, there is a well-established association of certain neoplasms with malformations of cortical development (cortical dysplasia), particularly dysembryoplastic neuroepithelial tumors and gangliogliomas. [17][18][19][20] The purpose of this study is to systematically review one institution's experience with neoplasms associated with identifiable coexistent pathology arising in the setting of chronic epilepsy.…”
mentioning
confidence: 99%
“…Using chronic subdural electrode recording, an interictal electrocorticogram (ECoG) demonstrated that the medial temporal lobe lesion and the FCD lesion exhibited independent paroxysmal discharges, while an ictal ECoG demonstrated that the medial temporal lobe was the ictal onset zone. We postulated that the FCD lesion Introduction 'Dual pathology' in patients with temporal lobe epilepsy (TLE) refers to the coexistence of hippocampal sclerosis (HS) and extrahippocampal lesions such as focal cortical dysplasias (FCD), vascular malformations including cavernoma (CA), and primary benign brain tumors including ganglioglioma, dysembryoplastic neuroepithelial tumors, pleomorphic xanthoastrocytomas, and low grade astrocytomas [1,2,3]. We report herein a rare case of TLE with triple pathology of HS, and FCD and CA in the ipsilateral frontal lobe.…”
mentioning
confidence: 99%